2016
DOI: 10.1016/j.homp.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula

Abstract: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…37 The studies performed by this group in the 2010s had a new and different focus: to document pro-apoptotic effects of homeopathic medicines on cancer cells and establish their underlying mechanisms. [40][41][42][43][44][45] In all these cases, they reported positive findings-cytotoxic action, involving several signal 47 The hypothesis that homeopathic medicines only hinder the viability of tumor cells, without any cytotoxic activity on normal ones, was tested by Wani et al, 48 and Frenkel et al, 49 both of which groups analyzed drugs and cancer models included in the Banerjee protocol. Against this evidence, however, Wälchli et al 50 hypothesized and demonstrated that primary cells are fitter to respond to high potencies than cell lines, especially cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The studies performed by this group in the 2010s had a new and different focus: to document pro-apoptotic effects of homeopathic medicines on cancer cells and establish their underlying mechanisms. [40][41][42][43][44][45] In all these cases, they reported positive findings-cytotoxic action, involving several signal 47 The hypothesis that homeopathic medicines only hinder the viability of tumor cells, without any cytotoxic activity on normal ones, was tested by Wani et al, 48 and Frenkel et al, 49 both of which groups analyzed drugs and cancer models included in the Banerjee protocol. Against this evidence, however, Wälchli et al 50 hypothesized and demonstrated that primary cells are fitter to respond to high potencies than cell lines, especially cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Wani et al 2016 48 40 to 5% alcohol (pre-test); untreated cells (negative). potencies (known as "potency chord") 60 is still an open field for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicodendron pubescens (known in Homeopathy as Rhus toxicodendron ) exhibited anti-inflammatory effect on rat arthritis [59] ; the maximum protective effect was evident in the crude form at 10 mg/kg/day, but significant results were obtained also with Homeopathic dilutions 3c, 6c, 30c, and 200c. Terminalia chebula , which is a component of the Ayurvedic formulation Triphala [60] , showed a dose-dependent anti-proliferative activity against cancer cell lines when tested as low dilutions or crude ethanolic extract [61] , [62] but also as Homeopathic preparations 6c and 30c [63] . It has been suggested that T. chebula extract and other Indian plants with anticancer properties may act by enhancing Fenton reaction-mediated damage to deoxynucleoside triphosphates, thus slowing down DNA replication in rapidly dividing cancer cells [64] .…”
Section: Discussionmentioning
confidence: 99%
“…Drug-DNA interaction was implicated in this phenomenon. Interestingly, recent studies showed existence of nanoparticlelike structures in some homeopathy formulations (239,(263)(264)(265). In this regard, it would be relevant to investigate anti-HPV effects and mechanism of action of these homeopathic drugs.…”
Section: Anti-hpv Leads In Alternative Medicinesmentioning
confidence: 99%